The Roles of School Principal Leadership in Developing English Teachers’ Creativities in Palu - Abdul Gafur Marzuki; Saja'un Lampuasa (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This research is a descriptive qualitative that explaines and describes any pertinent things related to the school principal leadership and teachers’ creativities which occur now at the research spot. This study aims to investigate the roles of the school principal in encouraging, driving, and directing teachers to be creative in performing their works. Results indicated that in encouraging his teachers, the school principal: 1) provides conducive climate and condition by involving his teachers in designing school programs and by welcoming his teachers’ comments and arguments on any policies he applies or any decisions he takes; 2) introduces and assures his teachers that education paradigm has changed therefore the school should be managed as a business firm in the area of public services where the most thing that should be considered is how to satisfy customers; 3) informs clearly that in evaluating the staffs’ performances he applies reward and punishment policy; and 4) optimizes managerial functions especially in monitoring what happens in the classroom. In driving the teachers, the school primcipal should applies his or her policy and delegates several responsibilities and jobs to the right persons. In directing the teachers he or s lets his or staffs free to do their best.